Lateral pharyngeal wall collapse associated with hypoxemia in obstructive sleep apnea. (13th January 2015) - Lan, Ming‐Chin; Liu, Stanley Y. C.; Lan, Ming‐Ying; Modi, Rahul; Capasso, Robson
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Review drug‐induced sleep endoscopy (DISE) findings and correlate the patterns of airway collapse with body mass index (BMI) and objective sleep study respiratory variables, with particular emphasis on oxygen desaturation variables. Study Design Retrospective chart review. Methods From January 2010 to March 2014, 64 patients underwent DISE, and its findings were registered using the VOTE (velum, oropharynx, tongue base, epiglottis) classification system. Associations were analyzed between DISE, BMI, and polysomnographic parameters. Results Complete lateral oropharyngeal collapse was significantly associated with increased severity of obstructive sleep apnea (OSA), reflected by a higher oxygen desaturation index, apnea‐hypopnea index, apnea index, the percent of the total time with oxygen saturation level lower than 90%, and minimal oxygen saturation). Complete concentric collapse of the velum and complete lateral oropharyngeal collapse were associated with higher BMI values. Conclusions The results of this study demonstrate a strong association between complete lateral oropharyngeal wall collapse and increased OSA severity, particularly with objective oximetry measures. Patients with a complete lateral oropharyngeal wall collapse may need aggressive treatment strategies because of the high probability of subsequent cardiovascular complications. Level of Evidence 4 Laryngoscope, 125:2408–2412, 2015